All dolled up - new future for Avenir - Young, Quentin, author; A&E Spotlight, publisher (Colorado State University. Libraries, 2016)
Article from A&E Spotlight about the renovations and exhibits at Avenir Museum.
Keywords: Fashion -- History; Fashion -- Exhibitions